Empowering Aceh's SMEs Mentors: A Journey of Excellence in Competence Development for Sustainable Growth - Yusrizal, Yusrizal; Sentosa, Dewi Suryani; Halim, Hendra; Majid, M. Shabri Abd.; Mazwan, Rasmuna; Sasra, Said Fachrizal; Nasir, M. Fadhil; Zulfa, Zulfa; Ridmailis, Ridmailis; Maira, Hayatun; Dewi, Annisa Keumala (Jurnal Pengabdian Bakti Akademisi, 2024)
This community service initiative aims to enhance the competence Mentors of Small and Medium Enterprises (SMEs) in Aceh, Indonesia, by identifying and analyzing best practices adopted by successful SMEs. The global economic landscape, coupled with challenges exacerbated by the COVID-19 pandemic, has highlighted the need for SMEs to improve their competitiveness and product quality. By focusing on enhancing the competence of SME owners through service learning, this initiative seeks to empower SMEs in Aceh and contribute to economic development. The methods include planning, problem identification, solution development, implementation, and evaluation. Results indicate that implementing best practices such as employee training, attention to work equipment, and improved customer service can significantly impact business performance and growth. The findings are relevant to theories of business growth and are applicable not only to SMEs in Aceh but also to SMEs in other regions. This initiative contributes to the achievement of Sustainable Development Goals (SDGs) related to economic growth and poverty alleviation. Overall, this initiative provides practical insights and strategies for SMEs to enhance their competitiveness and contribute to sustainable development.